EVALUASI KELAYAKAN PABRIK KARET DI KABUPATEN SINTANG PROVINSI KALIMANTAN BARAT - Burhansyah, Rusli (Indonesian Journal of Socio Economics)
The building opportunity of rubber agroindustry in West Kalimantan Province especially in Sintang Regency is good enough. This matter is supported broadly plant area in Sintang Regency until year 2005 for the width of 65.681 Ha or 12,79% of total wide of that province.Â  Survey, observation, and interview are used to collect data of farmerâs characters. Method of data analyse use the indicator of investment feasibilty i.e.: Economic Advantage, Net Present Value , Return (IRR), Benefit Cost Ratio (B/C ratio), and Rate of Return Invesment.Â  Sensitivity Analyze is used to anticipate the input change especially labour cost increase, raw material increase,Â  inflation, electricity, and fuel. Â Â Â  Â The analyse result shows: (1) The investation of mini Compo Crepe Factory is not feasible. Its causedÂ  by theÂ  small scale capacity of product only 10 ton/ month; (2)Â  It can be more feasible if that capacity more than 35 ton /month so the NPV as same as Rp 2.746.138.515, IRR > 50%, Gross B/CÂ  > 1, and payback period in the second year; (3) On the level ofÂ  production capacity as same as 140 ton/monthÂ  (as a development plan), Mini Factory Compe Crepe invesment is feasible, so the existence of expended operation change (UMR, raw material increase, and inflation, electricity and BBM) to adjust the expended operation calculation. In the case of expended increase (UMR, raw material increase, inflation, electricity and BBM), it must be excuted by a price compatibility; and to plan of factory development can be done byÂ  mangel machine instalation at 140 ton/month of production capacity. The capital scarcityÂ  of factory operation can be strived by loan of banking institute. In order to make more feasible condition can be done by laboured improvement and repaired infrastructure of road; so the street can be passed by any kindÂ  ofÂ  transportationÂ  mode which can supply raw material easily. Â